Cooperative Catalysis: Enantioselective Propargylic Alkylation of Propargylic Alcohols with Enecarbamates Using Ruthenium/Phosphoramide Hybrid Catalysts1. Issue 13 (4th February 2015) - Senda, Yasushi; Nakajima, Kazunari; Nishibayashi, Yoshiaki
Abstract The diastereo‐ and enantioselective propargylic alkylation of propargylic alcohols with E‐enecarbamates in the presence of a catalytic amount of thiolate‐bridged diruthenium complexes bearing an optically active phosphoramide moiety gives the corresponding propargylic alkylated products (up to 97 % ee).